General Characteristics for Loading the Working Elements of Drilling and Milling Machines when Moving in the Clay Solution - Adil Kadyrov; Zhanara Zhunusbekova; Aleksandr Ganyukov; Irina Kadyrova; Aliya Kukesheva (Communications - Scientific letters of the University of Zilina, 2021)
The article is devoted to influence of the clay thixotropic solutions on the strength of resistance to movement of the earthmoving machines' working elements.The forces of resistance to the movement of a flat plate, a smooth cylinder and real working bodies in a clay solution for various modes of solution flow (bingamian, pseudo-laminar and turbulent) are established.Mathematical models of movement of the earthmoving machines working elements in clay solution are developed and investigated.Dynamics of the working element of an earthmoving machine movement in a clay solution is studied. Dependence of the feed force, torque and dynamic coefficient on the resistance forces, acting on the working body from the clay solution, is established.